2013
DOI: 10.1007/s00405-013-2415-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of three MDCT post-processing protocols: preoperative assessment of the ossicular chain in otitis media

Abstract: The aim of this study was to examine and assess comparative values of HRCT-based multiplanar reformation (MPR), volume rendering (VR) and virtual endoscope built on three-dimensional (3D) shaded-surface display (SSD-based CTVE) for detections of ossicular chain's damage in patients with otitis media. 70 human ears from 70 patients suffering by chronic otitis media or cholesteatoma, who were examined with a preoperative multi-slice computer tomography (MSCT) examination and tympanoplasty in our hospital were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Two main types include acute otitis media (AOM) and otitis media with effusion (OME), although they are rather a continuum of disease. The aetiology of OM is complex and includes multiple interacting factors, which are, among others, host factors (allergy, immunocompetence and genetic predisposition), anatomic/physiologic features (mainly related to the Eustachian tube), infections (viral and bacterial) and environmental factors (tobacco smoke exposure, air pollution and socio-economic status) (Casselbrant and Mandel, 2010;Ilechukwu et al, 2014;Qureishi et al, 2014;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two main types include acute otitis media (AOM) and otitis media with effusion (OME), although they are rather a continuum of disease. The aetiology of OM is complex and includes multiple interacting factors, which are, among others, host factors (allergy, immunocompetence and genetic predisposition), anatomic/physiologic features (mainly related to the Eustachian tube), infections (viral and bacterial) and environmental factors (tobacco smoke exposure, air pollution and socio-economic status) (Casselbrant and Mandel, 2010;Ilechukwu et al, 2014;Qureishi et al, 2014;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of risk factors for chronic and recurrent OM revealed the impact of, among others, allergy, upper respiratory tract infections, low socio-economic status (poor housing, environmental and occupational conditions), lack of breastfeeding and genetic predisposition (Zhang et al, 2014). Among various sociodemographic risk factors for COM development in modern suburban Nigerian children, only malnutrition, low social status and indoor-cooking were significant (Lasisi et al, 2007).…”
mentioning
confidence: 99%
“…As a cautionary note, care should be taken when comparing the results of CBCT to literature of conventional CT published over a decade ago as post-processing modules have been subject to marked advances in recent years. Hence, more recent reports for multislice CT demonstrated that MPR and VolRen were relatively dependable for representation of small bony objects such as the ossicles (Zhang et al, 2014), and some even postulated, based on extremely high agreement, that MPR and VolRen measurements could be interchangeable (Magarelli et al, 2012).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…Otitis media (OM) is a group of complex infective and inflammatory conditions, with a variety of subtypes differing in signs and symptoms, complications and treatment (Qureishi et al 2014). The etiology of OM is complex and includes multiple interacting factors, which are, among others, host factors, anatomic/ physiologic features, infections (viral and bacterial) and environmental factors (tobacco smoke exposure, air pollution and socio-economic status) (Casselbrant and Mandel 2010;Ilechukwu et al 2014;Qureishi et al 2014;Zhang et al 2014). In the majority of children, viral infection of the upper respiratory tract initiates the cascade of events that finally leads to the development of OM.…”
Section: Otitis Mediamentioning
confidence: 99%